In vitro evaluation of the inhibition and induction potential of olaparib, a potent poly(ADP-ribose) polymerase inhibitor, on cytochrome P450. (3rd June 2018) - McCormick, Alex; Swaisland, Helen; Reddy, Venkatesh Pilla; Learoyd, Maria; Scarfe, Graeme
Abstract: 1. In vitro studies were conducted to evaluate potential inhibitory and inductive effects of the poly(ADP-ribose) polymerase (PARP) inhibitor, olaparib, on cytochrome P450 (CYP) enzymes. Inhibitory effects were determined in human liver microsomes (HLM); inductive effects were evaluated in cultured human hepatocytes. 2. Olaparib did not inhibit CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2D6 or CYP2E1 and caused slight inhibition of CYP2C9, CYP2C19 and CYP3A4/5 in HLM up to a concentration of 100 μM. However, olaparib (17–500 μM) inhibited CYP3A4/5 with an IC50 of 119 μM. In time-dependent CYP inhibition assays, olaparib (10 μM) had no effect against CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6 and CYP2E1 and a minor effect against CYP3A4/5. In a further study, olaparib (2–200 μM) functioned as a time-dependent inhibitor of CYP3A4/5 ( K I, 72.2 μM and K inact, 0.0675 min −1 ). Assessment of the CYP induction potential of olaparib (0.061–44 μM) showed minor concentration-related increases in CYP1A2 and more marked increases in CYP2B6 and CYP3A4 mRNA, compared with positive control activity; however, no significant change in CYP3A4/5 enzyme activity was observed. 3. Clinically significant drug–drug interactions due to olaparib inhibition or induction of hepatic or intestinal CYP3A4/5 cannot be excluded. It is recommended that olaparib is given with caution with narrow therapeutic range or sensitive CYP3A substrates, and that prescribers are aware that olaparib may reduce exposure to substrates of CYP2B6.